2011
DOI: 10.1111/j.1748-5827.2011.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of signalment on developing cranial cruciate rupture in dogs in the UK

Abstract: Cranial cruciate ligament rupture is more likely in Rottweilers and in female dogs, older dogs and obese dogs. Following multi-variable analysis, it was established that neutering was not associated with increased risk of cranial cruciate ligament rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
61
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 11 publications
8
61
5
Order By: Relevance
“…rottweilers and Golden retrievers have been cited as breeds in which CCL disease is common (haraSeN, 2003). Compared to the studies by haraSeN et al (2003), aDaMS et al (2011 and taYLOr-BrOWN et al (2015), we noticed a lower incidence of CCL rupture in rottweilers (5.1%) and in West highland terriers and Yorkies (0.85%). On the other hand, Labradors and mixed breeds had a greater incidence of CCL rupture (21%).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…rottweilers and Golden retrievers have been cited as breeds in which CCL disease is common (haraSeN, 2003). Compared to the studies by haraSeN et al (2003), aDaMS et al (2011 and taYLOr-BrOWN et al (2015), we noticed a lower incidence of CCL rupture in rottweilers (5.1%) and in West highland terriers and Yorkies (0.85%). On the other hand, Labradors and mixed breeds had a greater incidence of CCL rupture (21%).…”
Section: Resultscontrasting
confidence: 84%
“…Dogs aged 5 years and older had 2.5 times the odds of CCL rupture compared with dogs aged less than 5 years, P<0.01. there is a strong breed-related predisposition to CCL rupture in dogs (BaIrD, 2014). West Highland White Terriers, Yorkshire Terriers and Rottweilers had a significantly higher prevalence of CCLR, and Rottweilers had five times greater incidence compared with other pure breeds, with females twice as likely to suffer CCLr compared to males (aDaMS et al, 2011). In our retrospective study, dogs younger than 2 years accounted for only 2.6% of total dogs, and those older than 8 accounted for almost 31%.…”
Section: Resultsmentioning
confidence: 59%
“…The evidence for a protective role of sex hormones in ligament integrity can be seen in the presence of gonadal hormone receptors on ligaments [41], the increase of ligament elastin content and fiber diameter in response to estrogen administration [42], and the greater likelihood of cruciate injury in female athletes when estrogen is low [43]. However, obese dogs are four times more likely to rupture their cranial cruciate ligament [44] and neutering is a factor highly associated with the development of obesity, with neutered females being more prone than neutered males [45]. An obesity association, distinct from the gonadal hormone role, driving the observed increase in RACL cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported prevalence estimates for CCL disease in dogs from 1.2% to 2.6% and identified risk factors including breed, sex, neutering, age, and bodyweight . A study of 1.25 million dogs in the USA from a predominantly referral population over a 40‐year period identified the 5 breeds most commonly affected as the Newfoundland, Rottweiler, Labrador Retriever, Bulldog, and Boxer .…”
mentioning
confidence: 99%
“…A study of 1.25 million dogs in the USA from a predominantly referral population over a 40‐year period identified the 5 breeds most commonly affected as the Newfoundland, Rottweiler, Labrador Retriever, Bulldog, and Boxer . Subsequent studies have confirmed increased prevalence in the Labrador Retriever, Newfoundland, Boxer, and Rottweiler as well as reporting predispositions in other breeds including the West Highland White Terrier, Yorkshire Terrier, Golden Retriever, Staffordshire Bull Terrier, Neapolitan Mastiff, Akita, Saint Bernard, Mastiff, Chesapeake Bay Retriever, and American Staffordshire Terrier …”
mentioning
confidence: 99%